Caracterización físico-química y sensorial de treinta materiales élites de cacao (Theobroma cacao l.) - Chévez Vera, Héctor David (2015)
The aim of the present study was to determine physical and chemical characteristics and sensory quality almond paste cocoa clones elites thirty cocoa (Theobroma cacao L.) in the Experimental Farm " The Represa " property of the State Technical University Quevedo had last January 15 to April 14, being considered rainy season, a design completely randomized was used with thirty treatments and two replications each experimental unit was constituted 10 physiologically ripe fruit. More representative the results regarding the given physical quality T30 (23.00) witness; T12 (12.00); T17 (12.00) with the best indicators of healthy pods, the best rates kg ha-1 of dry fermented cocoa and witness the results T30 (1930.00) and T18 (790.00), top seed rates at present T18 (2.00) and T8 (1.53) for superiority in weight, witness T30 (13.06); T12 (16.00) and T28 (16.50) were higher and gave the best rates ears concerning the cutting test total fermentation led to optimal results T9 (99.50) and T23 (99.00), with the highest concentration almonds color T29 were violet light (5.00) and T30 witness; T13; 8; 2 and 3 (4.00) on the chemical quality T18 (8.16) and T5 (10.47) were the best indicators of protein while treatments witness T30 (43.45) and T 28 (38.65) had superiority in terms of percentage of fat. Concerning the sensory quality reflecting the floral taste to T2 (7) achieving superiority also considered cocoa up to T1; T5 and T8 (6). T3; T4; T13; T15 and T19 got (5) being higher. (6) was the value T1; T2; T3; T5; T8; T11 in the cocoa flavor, (7) T19 paste was privileged in the fruity flavor and (3) current in T1 and T28 on the nutty flavor. About the best treatments we recommend inquiring with analysis such as theobromine and caffeine to determine the superior quality